Effectiveness of Listening to the Murottal Al-Qur'an with the Nagham Bayyati Rhythm in Improving Concentration Ability in Fathul Ulum Banyuwangi Madrasah Ibtidaiyah (MI) Students - Wibowo, Tri Suryo; Aprilyawan, Grenda (Griya Eka Sejahtera, 2024)
Background: Murottal is the reading of the Qur'an in accordance with the tajwid plus tartil (slowly and not in a hurry so that the makhrijul letters are conveyed clearly and correctly). The comfort of female students in listening to murottal Al-Qur'an, if it is listened to at a tempo of between 60-70 BPM in a stable manner, without sudden changes in rhythm, and in a soft tone, it will create a feeling of comfort for the female students so that their minds can be more concentrated and focused on one object. This research aims to measure the level of effectiveness of murottal al-Quran on students' concentration levels.Methods: This type of research is quantitative research using quasi-experimental methods. The sample used was 40 students of Madrasah Ibtidaiyah (MI) Fathul Ulum Muncar Banyuwangi. The data collection technique uses the digit span forward and backward test.Results: This research was carried out at Madrasah Ibtidaiyah (MI) Fathul Ulum Muncar Banyuwangi. This research was conducted on 14 – 19 June 2024 with a total of 40 respondents. The data obtained was then processed with the help of the Statistical Package for the Social Sciences 24 (SPSS 24) program.Conclusion: There is a significant influence between listening to murottal Al-Qur'an in the rhythm of Nagham Bayyati and increasing concentration in students at Madrasah Ibtidaiyah (MI) Fathul Ulum Muncar Banyuwangi